Analysis of Grade 10 Opportunity-to-Learn Dynamics of Market from Two Economics Textbooks - Ijeoma C. Ogbonnaya (Economic Education Analysis Journal, 2023)
This theoretical paper analyses the Opportunity-to-Learn (OTL) Dynamics of Market offered in two Grade 10 economics textbooks. The study asked whether opportunities provided in economics textbooks improve learners’ performance in Dynamics of Market. Following a Content Analysis approach, three OTL variables; Content organization, Content coverage and Tasks were used as the theoretical framework to couch this study. One of the findings was that Less High-Order tasks were found in both textbooks hence do not develop learners’ Higher order Cognitive skills. The overall study showed that the analysed economics textbooks do not offer enough OTL Dynamics of Market. This study is significant because it helps both educators and policy makers to explore more on ‘must-have features’ of economics textbook before it could be prescribed for use. It makes contribution to international literature on textbook analysis in the field of economics education, this is rare in economics education studies. It is recommended that Higher order tasks should be included in future editions of the Grade 10 economics textbooks thus, suggesting the need to analyse economics textbooks in high schools for effective learning. Although the study analysed specific textbooks, its findings shed light on how learning opportunities relate to performance more generally.